The formation of a mercantilist state and the economic growth of the United Kingdom 1453 - 1815 - Patrick Karl O'Brien (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
New institutional economics lacks a theory of state formation which could help us to deal with the mega question of why some states became more efficient than others at establishing and and sustaining institutions. Some kind of middle range theory could be formulated based upon historical case studies. This paper considers the case of Britain and as its title suggests degrades the myth of the United Kingdom as the paradigmn example of liberalism and laisser faire. In making its precocious transition to and industrial market economy the kingom's history is best represented as a case of successful mercantilism. – military ; sovereignty ; mercantilism ; political economy ; taxation
Keywords: E62; P16; F59; 330; Merkantilismus; Großbritannien